PUBERTAL DEVELOPMENT IN BOYS WITH UNILATERAL CRYPTORCHIDISM - N. Y. Raygorodskaya; D. A. Morozov; N. V. Bolotova; L. N. Sedova; N. B. Zacharova (Вестник урологии, 2014)
The results of a prospective study of 32 boys 11-15 years, underwent orchiopexy about unilateral cryptorchidism are presented in article. The evaluation of pubertal development, testicular ultrasound and doppler, prostate investigation and the tests of serum reproductive hormones were performed. The examination were found the reduced gonads volume side orhiopexy determined at the initiation of puberty and expanded as it progresses, degenerative changes of the prostate gland . There were not significant changes in serum gonadotropins and testosterone.